2023
DOI: 10.1109/te.2023.3273352
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Sources Fostering First-Year Engineering Students’ Academic Well-Being in a PBL Environment

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research.-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…• Real-World Relevance: PBL often involves realworld, authentic problems. By connecting learning to practical applications, it can make engineering education more appealing and relevant to a diverse range of students (Chen et al, 2023). • Student-Centered Approach: The studentcentered nature of PBL acknowledges and values the individual experiences and perspectives of learners.…”
Section: Summary and Opinionsmentioning
confidence: 99%
“…• Real-World Relevance: PBL often involves realworld, authentic problems. By connecting learning to practical applications, it can make engineering education more appealing and relevant to a diverse range of students (Chen et al, 2023). • Student-Centered Approach: The studentcentered nature of PBL acknowledges and values the individual experiences and perspectives of learners.…”
Section: Summary and Opinionsmentioning
confidence: 99%
“…The study by Juebei Chen et al explored factors that promoted academic well-being among first-year engineering students in a PBL environment. Their research found that teacher support and active participation, peer collaboration and atmosphere, and the relevance of course content were all important factors that influenced students' academic well-being [4]. A PBL intervention study conducted by Oscar I. Higuera-Martinez et al aimed at cultivating the creativity of first-year engineering students found that PBL-based interventions can significantly improve students' creative performance and problem-solving abilities [5].…”
Section: Related Workmentioning
confidence: 99%